Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

inverse functionf(x)= 1/2 (3-3x)

Sagot :

f(x)= 1/2 (3-3x) ​

First, write as a linear equation: (replace f(x) by y)

y= 1/2 (3-3x)

Swap x and y variables:

x = 1/2 (3-3y)

Solve for y:

x = 1/2(3)+1/2(-3y)

x= 3/2 -3/2y

x-3/2 = -3/2y

(x-3/2) / -3/2 = y

-2/3x+1=y

Write in inverse notation

f-1(x) = -2/3x+1